Youth Political Participation: The Case of Lithuania - Dilytė, Asta; Lazutka, Romas (Socialinė teorija, empirija, politika ir praktika, 2017)
The goal of this paper is to analyze the political participation of youth in Lithuania. Political participation can be analyzed in different ways; in this work, the institutional structure of participation is analyzed. We use the rational choice neoinstitutionalism as a tool for the conceptualization of youth political participation. According to Elinor Ostrom, one of the representatives of rational choice neoinstitutionalism, an act ofpolitical participation is conditioned by seven sets of institutions as rules: position rules, boundary rules, choice rules, aggregation rules, information rules, payoff rules and scope rules. These are the elements of institutional structure of youth political participation in Lithuania that were analyzed. The institutions are written in legislation. The selected legislation was qualitatively analyzed using the software MaxQda 12.The results were grouped according with the seven sets of institutions that determine the actions of actors in an action arena. It can be said that there are opportunities for youths to participate in politics and policy implementation process. However, the main function of the youth is to provide information for policy makers. There are direct ways to get the opinion of youth related to certain policies – surveys, legislative initiatives, and indirect ways through collective agents, such as JRT, SJOT and LiJOT. The political participation of youths requires a lot of expenses (especially in human resources, headquarters establishment and management as well as other material resources and access to mass media), but the benefits of political participation are weak.
Keywords: Political participation; Youth; Neoinstitutionalism; Lithuania